The Effect of YouTube-Based Learning Media on Students’ Achievement in Akidah Akhlak at the Madrasah Tsanawiyah Level - Tien Azhari Ni’madina; Alfian Eko Rochmawan; Muhammad Fatchurrohman (Ashlach : Journal of Islamic Education, 2026)
This study aims to analyze the effect of using YouTube media in Akidah Akhlak learning on the learning outcomes of eighth-grade students at MTsN 3 Sukoharjo, Indonesia, as a response to the growing need for digital learning media in religious education. The study employed a quantitative approach with a correlational survey design involving 43 students drawn from a total population of 172 students. Data were collected through a 20-item Likert-scale questionnaire to measure the use of YouTube media and through documentation of students’ midterm assessment scores. The data were then analyzed using descriptive statistics, a normality test, a linearity test, and Pearson Product-Moment correlation with the assistance of SPSS version 25. The results showed that the use of YouTube media was in the moderate category (70%), while students’ learning outcomes were also in the moderate category (60%). Statistical analysis indicated that there was no significant effect between the use of YouTube media and students’ learning outcomes, with a correlation value of r = -0.088 and a coefficient of determination of R² = 0.008, meaning that the use of YouTube media contributed only 0.78% to students’ learning outcomes. These findings suggest that, in the context of Akidah Akhlak learning, YouTube media functions more as a supporting learning medium than as a primary determinant of learning outcomes. Its effectiveness depends greatly on pedagogical integration, content relevance, and students’ readiness to engage in the learning process.